Epidemiology, Characteristic, and Prognostic Factors of Primary Sporadic Intradural Malignant Peripheral Nerve Sheath Tumor in the Spinal Canal: A Systematic Literature Review - Cao, Yue; Wang, Yu-Bo; Bai, Yang; Tan, Xuan-yu; Ma, Cheng-yuan; Chen, Yong; Yu, Hong-quan; Xu, Hai-Yang; Zhao, Gang (Frontiers in Oncology, 2022)
Purpose: Primary sporadic intradural malignant peripheral nerve sheath tumor (MPNST) in the spinal canal is a type of rare neoplasm with challenging diagnosis and therapy. The overall prognosis of this tumor is markedly different from that of the usual spinal intradural tumors. The purpose of this systematic review is to reduce the misdiagnosis and enhance the prognosis of the disease by reviewing the literature. Methods: PubMed, Medline, and Embase databases were searched for articles in English language published from 1980 to May 2021, yielding 500 potentially relevant articles. The Keywords were as follows: "spinal", "malignant peripheral nerve sheath tumor", "neurosarcoma", "malignant schwannoma" and "malignant neurofibroma". 13 papers met the eligibility criteria, including 55 cases with spinal intradural primary sporadic MPNSTs which were confirmed by post-operation pathology. We further analyzed the clinical manifestations, radiological manifestations, pathological features, comprehensive treatment strategies and prognosis. Results: Fifty-five spinal intradural primary sporadic MPNSTs in 30 (54.5%) male and 25 (45.5%) female with an average age at diagnosis of 40 years (range 3-70 years) were recruited. The most common clinical manifestations were local or radicular pain and motor disturbance. All tumors had significant enhancement and heterogeneous enhancement was more common. 14/18 lesions were diagnosed as high-grade and the remaining 4 were diagnosed as low-grade. The ki-67 labeling index ranged from 5% to 60%. The median recurrence and survival time were 36 and 72 months respectively. The log-rank tests indicated that significant predictors of OS were patient age (≤30 vs >30 years) at the time of diagnosis and the presence of metastatic disease, and similar analyses for RFS demonstrated the presence of metastatic disease was the only significant predictor (60 vs 10 months). The multivariate Cox proportional hazards regression analysis revealed that no metastasis was an independent factor for predicting a favorable prognosis. Conclusions: Spinal intradural primary sporadic MPNSTs are challenging malignant tumors without systematic treatment plan. The factors affecting its prognosis are not clear. Even after surgical treatment and adjuvant treatment, the recurrence rate and mortality rate are still high. Clinicians should be alert to the possibility of this disease and achieve early detection and treatment.